Prosthetic Joint Infection due to Histoplasma capsulatum in a Patient from Trinidad: Workup, Pathology, and Treatment. (5th August 2022) - Satalich, James; Reznicek, Julie; Bryson, Alexandra; Pershad, Prayag; Hooper, Nicholas; Satpathy, Jibanananda
Abstract : Histoplasma capsulatum is a rarely reported cause of prosthetic joint infections. This current case report is of a patient from Trinidad, with a history of a right total knee replacement (TKR), who underwent a successful two-stage revision due to a Histoplasmosis capsulatum periprosthetic joint infection (PJI). This case report offers a unique treatment plan to successfully treat Histoplasmosis capsulatum periprosthetic joint infections and emphasizes the importance of obtaining an accurate travel history.